2019
DOI: 10.1186/s12889-019-6406-0
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus gastroenteritis in Indian children < 5 years hospitalized for diarrhoea, 2012 to 2016

Abstract: BackgroundIn 2016, the Government of India introduced the oral rotavirus vaccine (ROTAVAC, Bharat Biotech, India) in 4 states of India as part of the Universal Immunization Programme, and expanded to 5 more states in 2017. We report four years of data on rotavirus gastroenteritis in hospitalized children < 5 years of age prior to vaccine introduction.MethodsChildren from 7 sites in southern and northern India hospitalized for diarrhoea were recruited between July 2012 and June 2016. Stool samples were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 21 publications
10
39
0
1
Order By: Relevance
“…This nding is identical to a monitoring analysis by Yu et al on the seasonality of RVA infection [30]. The same patterns have also been reported in other Asian countries like Pakistan [23] and India [28]. However, according to the WHO, RVA prevalence was reported throughout the year in the subtropical zone and peaks often occur in dry seasons, unlike in the northern hemisphere countries where peaks occur in winter [31].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This nding is identical to a monitoring analysis by Yu et al on the seasonality of RVA infection [30]. The same patterns have also been reported in other Asian countries like Pakistan [23] and India [28]. However, according to the WHO, RVA prevalence was reported throughout the year in the subtropical zone and peaks often occur in dry seasons, unlike in the northern hemisphere countries where peaks occur in winter [31].…”
Section: Discussionsupporting
confidence: 87%
“…Available data suggest that RVA is susceptible to people of any age but spreading more easily among infants and young children [28]. Studies in Shanghai had discovered that the RVA prevalence was higher in children aged 3-5 years [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the variation in the prevalence of some uncommon genotypes (e.g., G9P[4] G9P[6], G3P[4], G3P[6]) detected after vaccine introduction in Mozambique, it is important to mention that a number of studies in Africa [ 16 , 25 , 32 ] and Asia (India and Japan) also reported these uncommon genotypes before vaccine introduction in low frequency [ 33 , 34 ]. These uncommon genotypes, apart from G9P[6], were also observed in Ireland before vaccine introduction [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the present findings, it was noted that the G1P[8] rotavirus circulated in Goa and was a cause of diarrhea in children and infants. The G1P[8] was the predominant rotavirus genotype (56.3% and 62.7%) observed during the surveillance studies during 2012–2016 ( Girish Kumar et al., 2016 ; Giri et al., 2019 ). In Meghalaya state, 3 strains showed P[8] and 2 showed P[4] genotypes specificity, while, the G genotype was not be typable.…”
Section: Resultsmentioning
confidence: 99%